Low transmissivity-energy absorption curtain grouting material proportion design method
Through the ratio design and performance optimization of the low transmittance-energy-absorbing curtain grouting materials, the problem of difficult to control the impact of blasting vibration on buried pipelines during urban tunnel blasting construction is solved, and effective shock absorption effect and construction efficiency are achieved.
Patent Information
- Application Number
- CN202411637206.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-15
AI Technical Summary
During the blasting construction of urban tunnels, the impact of blasting vibration on buried pipelines is difficult to control, and the construction of existing shock absorption measures is difficult, costly and difficult to quantify.
The grouting material of low transmittance-energy-absorbing curtain is used to determine the optimal ratio scheme through multi-factor, multi-level orthogonal test design, and combine rheological performance, physical and mechanical properties and energy-absorbing performance testing to optimize the performance of the grouting material, and verify the shock absorption effect through on-site blasting tests.
It effectively reduces the impact of blasting vibration on buried pipelines, provides reliable guarantees for underground pipeline protection and blasting project safety construction, simplifies the test workload, improves research efficiency, and quantifies shock absorption effects.
Smart Images

Figure CN119601141A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of underground engineering and blasting engineering, and in particular to a method for designing the proportion of low-transmittance-energy-absorbing curtain grouting materials. Background Art
[0002] As an economical and efficient means of underground engineering excavation, the drilling and blasting method is still one of the main methods of existing underground engineering excavation due to its advantages such as fast construction speed, low cost and strong adaptability. The drilling and blasting method is widely used in the development and construction of urban underground spaces such as tunnel projects, subway projects, and underground pipe galleries. Unlike mountain tunnels, urban tunnel blasting usually occurs in the underground rock layer in the city center. A large number of underground pipelines are usually laid in the urban soil layer, including municipal lifeline projects such as water supply and drainage pipelines, gas pipelines, and power pipelines. Therefore, during the blasting operation of tunnels under and near urban areas, the vibration disturbance effect will affect the safety of the buried pipeline structure in the overlying soil layer, which may cause safety hazards such as pipeline deformation, joint damage, and pipe body cracking, thereby posing a serious threat to engineering safety and the protection of people's lives and property in complex urban environments.
[0003] The seismic effect caused by blasting construction in urban areas is the primary problem of explosion hazards. Currently, the following three types of control measures are mainly adopted:
[0004] Take measures for the protected objects: such as reinforcing the pipeline, wrapping the protective layer, etc., but this method is difficult to construct and will affect the normal use of the pipeline;
[0005] Take measures against the explosion source: such as controlling the charge amount, adjusting the blasting parameters, etc., but this method will reduce the blasting efficiency and prolong the construction period;
[0006] Take measures during the propagation of blasting seismic waves: such as setting up shock-absorbing holes or shock-absorbing trenches, etc.
[0007] At present, the research on buried pipeline blasting vibration control technology focuses on taking control measures for the controlled objects and blasting sources. Although these two measures have certain effects, they have a great impact on the construction of blasting projects. As for taking measures for the attenuation and propagation of blasting seismic waves, shock-absorbing holes or shock-absorbing trenches are mainly used, but these methods have the following technical problems: the construction of shock-absorbing holes or shock-absorbing trenches is limited by site conditions and is often difficult to implement in densely populated urban areas; the shock-absorbing effect is significantly affected by depth and width, and the construction difficulty and cost increase accordingly; the shock-absorbing holes or shock-absorbing trenches themselves may affect the stability of the formation; the shock-absorbing effect is difficult to quantify and cannot be optimized in a targeted manner. Summary of the invention
[0008] In view of this, the present invention proposes a low-transmittance-energy-absorbing curtain grouting material ratio design method to solve the technical problems that the grouting curtain material ratio is difficult to determine and the shock-absorbing effect is difficult to quantify in urban tunnel blasting construction, thereby effectively reducing the impact of blasting vibration on buried pipelines and providing protection for underground pipeline network and safe construction of blasting projects.
[0009] The technical solution of the present invention is implemented as follows: The present invention provides a method for designing the proportion of low-transmittance-energy-absorbing curtain grouting materials, comprising:
[0010] S1. Select the basic proportion material of the grouting curtain, carry out multi-factor and multi-level orthogonal experimental design based on the basic proportion material, form n proportion schemes, pour the grouting material according to the n proportion schemes, obtain multiple samples for each proportion scheme, and number the samples according to the proportion scheme to which they belong;
[0011] S2. Perform rheological property tests on the samples, analyze the test results, and determine the order of influence of various factors on the rheological properties;
[0012] S3. Conduct indoor physical and mechanical property tests on the samples, analyze the test results, and determine the order of importance of various factors affecting the physical and mechanical properties;
[0013] S4. Conduct a split Hopkinson pressure bar test on the sample to obtain the energy dissipation curve of the sample, and determine the order of influence of various factors on energy absorption performance according to the energy dissipation curve;
[0014] S5. According to the results of steps S2-S4, determine the best ratio of the grouting material, and verify the rationality of the best ratio by combining the theoretical analysis of the transflective performance of the grouting material;
[0015] S6. Verify the shock absorption effect of the optimal ratio scheme through on-site blasting tests and calculate its shock absorption rate.
[0016] Based on the above scheme, the multi-factor multi-level orthogonal test in step S1 is a five-factor three-level orthogonal test. 27 (3 5 ) Orthogonal test table design experiment is carried out 3 3 = 27 kinds of mixing ratios, that is, n = 27; the five factors are:
[0017] Factor A: water-cement ratio; Factor B: iron powder mesh size; Factor C: iron powder content; Factor D: rubber mesh size; Factor E: rubber content.
[0018] On the basis of the above scheme, the rheological property test in step S2 includes a water separation rate test and a viscosity test, and the physical and mechanical property test in step S3 includes a density test, a uniaxial compressive strength test, an elastic modulus test and a longitudinal wave velocity test.
[0019] Based on the above solution, step S2 includes:
[0020] S21. The test method for water separation rate is as follows: the water separation amount is measured by using a measuring cylinder, the average value of multiple samples in each mixing ratio is taken as the water separation amount of the mixing ratio, the average value of the mixing ratios at multiple levels under the same factor is calculated, and a trend chart of the influence of each factor on the water separation rate is drawn, and the primary and secondary order of the influence of each factor on the water separation rate is obtained by analysis;
[0021] S22. The viscosity test method is: use a standard funnel viscometer to measure and correct the data, take the average value of multiple samples in each mix ratio as the viscosity of the mix ratio, calculate the average value of multiple levels of mix ratios under the same factor, and draw a trend chart of the influence of each factor on the viscosity, and analyze the order of priority of the influence of each factor on the viscosity.
[0022] Based on the above solution, step S3 includes:
[0023] S31. Density test method: use electronic balance to measure sample mass, use vernier caliper to measure sample height and diameter, calculate sample density according to mass-volume ratio, take the average value of multiple samples in each mix ratio as the density test result of the mix ratio, draw trend chart of factors affecting density, and analyze the order of influence of various factors on density;
[0024] S32. The uniaxial compressive strength test method is as follows: a uniaxial compressive test is performed using a pressure testing machine, the maximum axial force when the sample is damaged is recorded, the uniaxial compressive strength is calculated according to the cross-sectional area of the sample, the average value of multiple samples in each mix ratio scheme is taken as the uniaxial compressive strength test result of the mix ratio scheme, a trend chart of factors affecting the uniaxial compressive strength is drawn, and the order of importance of various factors affecting the uniaxial compressive strength is analyzed;
[0025] S33. The elastic modulus test method is as follows: during the uniaxial compression test, the axial stress and axial strain values of the sample in the elastic deformation stage are recorded, the elastic modulus is calculated according to the slope of the stress-strain curve, the average value of multiple samples in each ratio scheme is taken as the elastic modulus test result of the ratio scheme, a trend graph affecting the elastic modulus is drawn, and the primary and secondary order of the influence of various factors on the elastic modulus is analyzed;
[0026] S34. The longitudinal wave velocity test method is: use a pile foundation sonic tester to measure the sound wave propagation time of the sample, calculate the longitudinal wave velocity according to the sample height, take the average value of multiple samples in each mix ratio scheme as the longitudinal wave velocity test result of the mix ratio scheme, draw a trend chart of the factors affecting the longitudinal wave velocity, and analyze the order of priority of the factors affecting the longitudinal wave velocity.
[0027] Based on the above solution, step S4 includes:
[0028] S41, impact loading is performed on each sample, and the strain values on the incident rod and the projection rod of the sample during the impact process are recorded;
[0029] S42, drawing an energy dissipation curve of the sample according to the recorded strain value;
[0030] S43, calculating the energy transmittance ratio of each sample, and taking the average value of multiple samples in each ratio scheme as the energy transmittance of the ratio scheme;
[0031] S44. Calculate the average value of the multi-level ratio schemes under the same factor, draw a trend chart of the influence of each factor on the energy transmittance, and analyze the order of importance of each factor's influence on the energy absorption performance.
[0032] Based on the above scheme, in step S5, the process of determining the best ratio of grouting materials includes:
[0033] According to the requirements of the proportion of curtain grouting materials, set the energy absorption performance, density and longitudinal wave velocity as high priority;
[0034] According to the priority order of each factor's influence on water separation rate, the priority order of each factor's influence on viscosity, the priority order of each factor's influence on density, the priority order of each factor's influence on uniaxial compressive strength, the priority order of each factor's influence on elastic modulus, the priority order of each factor's influence on longitudinal wave velocity, the priority order of each factor's influence on energy absorption performance and priority setting, the optimal level of each factor is selected, the specific value of each factor is determined, and the best ratio scheme is formed.
[0035] On the basis of the above scheme, in step S5, the rationality of the optimal ratio scheme is verified by combining the theoretical analysis of the transflective performance of the grouting material, including:
[0036] Establish a transflection calculation model for grouting materials;
[0037] Based on the transflection calculation model, the P-wave and S-wave transmission coefficients of the best matching scheme under different incident angles are calculated;
[0038] Select the target incident angle and compare the transmission coefficient of the best ratio scheme with other ratio schemes;
[0039] The rationality of the optimal ratio scheme is verified by comparing the transmission coefficient results.
[0040] Based on the above solution, step S6 includes:
[0041] S61. Arrange acceleration sensors and earth pressure sensors in the on-site blasting test;
[0042] S62, forming a grouting curtain according to the optimal ratio scheme;
[0043] S63, respectively recording the acceleration and soil pressure data in the soil before and after the grouting curtain is formed;
[0044] S64. Compare and analyze the vibration propagation law and the change of pipeline strain before and after grouting;
[0045] S65. Calculate the damping rate of the grouting curtain based on the vibration parameters before and after grouting.
[0046] On the basis of the above scheme, the basic proportion materials of the grouting curtain are cement, rubber powder, iron powder and river sand.
[0047] Compared with the prior art, the present invention has the following beneficial effects:
[0048] 1. The present invention solves the technical problems of difficulty in determining the material ratio of grouting curtain and difficulty in quantifying the shock absorption effect in actual projects through systematic test design, performance testing, ratio optimization and actual verification, effectively reduces the blasting vibration peak of buried pipelines under the action of blasting vibration, and provides reliable guarantee for underground pipe network protection and safe construction of blasting projects;
[0049] 2. The present invention adopts a five-factor three-level orthogonal experimental design method, which simplifies the original 243 combinations into 27, while ensuring the representativeness of the test results, greatly reducing the test workload and improving research efficiency. Through the optimized combination of five key factors, namely water-cement ratio, iron powder mesh size, iron powder content, rubber mesh size and rubber content, the precise control of the performance of the grouting material is achieved;
[0050] 3. The present invention has established a comprehensive performance testing system, including the testing and analysis of rheological properties (water separation rate, viscosity), physical and mechanical properties (density, uniaxial compressive strength, elastic modulus, longitudinal wave velocity) and energy absorption performance. By analyzing the primary and secondary order of the influence of various factors on different performances, a scientific basis is provided for determining the best ratio scheme;
[0051] 4. The present invention combines the theoretical analysis of the transmissive and reflective properties of the grouting material with the actual blasting test, and ensures the reliability and practicality of the optimal ratio scheme through dual confirmation by theoretical calculation and actual verification, so that the shock-absorbing effect of the grouting curtain is fully verified and accurately quantified. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0053] Figure 1 is a flow chart of a method according to an embodiment of the present invention;
[0054] Figure 2 A test flow chart of an embodiment of the present invention;
[0055] Figure 3 This is a trend diagram of the influence of various factors on rheological properties in the embodiments of the present invention;
[0056] Figure 4 A trend diagram showing the influence of various factors on the physical and mechanical properties of an embodiment of the present invention;
[0057] Figure 5 A trend diagram showing the influence of various factors on the energy absorption performance of an embodiment of the present invention;
[0058] Figure 6 A schematic diagram of a transflection calculation model according to an embodiment of the present invention;
[0059] Figure 7 A comparison diagram of transmission coefficients of an embodiment of the present invention;
[0060] Figure 8 A schematic diagram of a blasting test design according to an embodiment of the present invention;
[0061] Fig. 9 This is a comparison chart of the shock absorption effect of the blasting test of the embodiment of the present invention. DETAILED DESCRIPTION
[0062] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0063] like Figure 1 As shown, the present invention provides a method for designing a ratio of a low-transmittance-energy-absorbing curtain grouting material, comprising:
[0064] S1. Select the basic proportion material of the grouting curtain, carry out multi-factor and multi-level orthogonal experimental design based on the basic proportion material, form n proportion schemes, pour the grouting material according to the n proportion schemes, obtain multiple samples for each proportion scheme, and number the samples according to the proportion scheme to which they belong;
[0065] S2. Perform rheological property tests on the samples, analyze the test results, and determine the order of influence of various factors on the rheological properties;
[0066] S3. Conduct indoor physical and mechanical property tests on the samples, analyze the test results, and determine the order of importance of various factors affecting the physical and mechanical properties;
[0067] S4. Conduct a split Hopkinson pressure bar test on the sample to obtain the energy dissipation curve of the sample, and determine the order of influence of various factors on energy absorption performance according to the energy dissipation curve;
[0068] S5. According to the results of steps S2-S4, determine the best ratio of the grouting material, and verify the rationality of the best ratio by combining the theoretical analysis of the transflective performance of the grouting material;
[0069] S6. Verify the shock absorption effect of the optimal ratio scheme through on-site blasting tests and calculate its shock absorption rate.
[0070] Specifically, currently, there are a variety of grouting curtain mix ratios to choose from. However, the application of grouting curtains is mainly concentrated in the fields of waterproofing and reinforcement, and the performance of grouting curtain mix ratios is also uneven, which cannot be well applied to urban blasting vibration control. At the same time, the rubber material in waste tires has excellent elastic properties and damping characteristics. Recycling and developing it into rubber-based shock-absorbing grouting materials has very important environmental protection and practical significance. Therefore, in the embodiment of the present invention, four materials, cement, rubber powder, iron powder and river sand, are selected as the basic mix ratio materials for the grouting curtain, such as Figure 2 shown.
[0071] In a specific embodiment of the present invention, a five-factor three-level orthogonal design is used. If a comprehensive experimental design is selected, three 5 = 243 combinations were tested. 27 (3 5 ) Orthogonal test table design test only needs 3 3 =27 schemes can be tested, and representative test results can be obtained at the same time, which greatly reduces the test workload, that is, in this embodiment, n=27. The five-factor three-level orthogonal header design is shown in Table 1. The five influencing factors are: factor A: water-cement ratio; factor B: iron powder mesh; factor C: iron powder content (%); factor D: rubber mesh; factor E: rubber content (%).
[0072] Table 1 Slurry ratio orthogonal test table design
[0073]
[0074] After a series of preliminary indoor tests, the specific values are shown in Table 2.
[0075] Table 2 Orthogonal test design scheme for slurry ratio
[0076]
[0077]
[0078] According to the 27 mix ratios shown in Table 2, the four materials were cast. Two specimens were prepared for each mix ratio, with the sizes The number of samples prepared for each ratio is 3, for example, 2 cylindrical samples and 1 cubic sample, or 1 cylindrical sample and 2 cubic samples, and each sample is numbered according to the test number in Table 2. The samples are then transferred to a standard curing box and tested after curing for 7 days under standard curing conditions of 20°C and 95% humidity.
[0079] Specifically, in one embodiment of the present invention, the rheological property test in step S2 includes a water separation rate test and a viscosity test. Step S2 includes:
[0080] S21. The test method for water separation rate is as follows: the water separation amount is measured by using a measuring cylinder, the average value of multiple samples in each mixing ratio is taken as the water separation amount of the mixing ratio, the average value of the mixing ratios at multiple levels under the same factor is calculated, and a trend chart of the influence of each factor on the water separation rate is drawn, and the primary and secondary order of the influence of each factor on the water separation rate is obtained by analysis;
[0081] S22. The viscosity test method is: use a standard funnel viscometer to measure and correct the data, take the average value of multiple samples in each mix ratio as the viscosity of the mix ratio, calculate the average value of multiple levels of mix ratios under the same factor, and draw a trend chart of the influence of each factor on the viscosity, and analyze the order of priority of the influence of each factor on the viscosity.
[0082] In a specific example, according to the orthogonal test scheme in Table 2, three samples are prepared for each mix ratio scheme, and the water loss of each sample is recorded by a measuring cylinder. The average water loss of the three samples cast for each mix ratio scheme is taken as the water loss of the mix ratio scheme. According to the orthogonal test design in Tables 1 and 2, the average values of the three levels under the same factor are calculated, and a trend chart of the influence of each factor on the water loss rate is drawn based on the average values of the three levels under the same factor, as shown in FIG. Figure 3As shown in (a) in . Figure 3 The horizontal axis of (a) represents the three level values corresponding to different factors. Through analysis, it can be seen that the order of importance of each factor on the water separation rate is A>C>E>D>B. The water separation rate test results of this embodiment are shown in Table 3. The range R in Table 3 refers to the difference between the maximum value and the minimum value. The order of importance of each factor is determined according to the size of the range R value. The larger the range, the more significant the influence of the factor.
[0083] Table 3 Results of orthogonal test on water separation rate
[0084]
[0085] The viscosity of the grouting curtain material is a physical quantity that measures the viscosity of a grouting liquid, that is, the size of the internal friction resistance. The size of the viscosity will directly affect the diffusion radius of the slurry, and ultimately have a certain impact on the grouting effect. Therefore, measuring the viscosity of the shock-absorbing grouting curtain material is of great significance for analyzing its rheological properties. The calculation formulas of each physical quantity in the test are as follows:
[0086]
[0087] Where: T1 is the correction value of viscosity; t is the viscosity value of the test water; T is the viscosity value of the test sample.
[0088] The data results were measured by a standard funnel viscometer and then corrected by combining with formula (1). The average viscosity of the three samples cast for each mix ratio was taken as the viscosity of the mix ratio. According to the orthogonal experimental design in Tables 1 and 2, the average values of the three levels under the same factor were calculated. The trend graph of the influence of each factor on the viscosity was drawn based on the average values of the three levels under the same factor, as shown in the figure. Figure 3 As shown in (b) in the figure. Through analysis, it can be seen that the order of influence of each factor on viscosity is A>C>B>E>D. The viscosity test results of this embodiment are shown in Table 4.
[0089] Table 4 Viscosity orthogonal test results
[0090]
[0091] Specifically, in one embodiment of the present invention, the physical and mechanical properties test in step S3 includes a density test, a uniaxial compressive strength test, an elastic modulus test, and a longitudinal wave velocity test. Step S3 includes:
[0092] S31. Density test method: use electronic balance to measure sample mass, use vernier caliper to measure sample height and diameter, calculate sample density according to mass-volume ratio, take the average value of multiple samples in each mix ratio as the density test result of the mix ratio, draw trend chart of factors affecting density, and analyze the order of influence of various factors on density;
[0093] S32. The uniaxial compressive strength test method is as follows: a uniaxial compressive test is performed using a pressure testing machine, the maximum axial force when the sample is damaged is recorded, the uniaxial compressive strength is calculated according to the cross-sectional area of the sample, the average value of multiple samples in each mix ratio scheme is taken as the uniaxial compressive strength test result of the mix ratio scheme, a trend chart of factors affecting the uniaxial compressive strength is drawn, and the order of importance of various factors affecting the uniaxial compressive strength is analyzed;
[0094] S33. The elastic modulus test method is as follows: during the uniaxial compression test, the axial stress and axial strain values of the sample in the elastic deformation stage are recorded, the elastic modulus is calculated according to the slope of the stress-strain curve, the average value of multiple samples in each ratio scheme is taken as the elastic modulus test result of the ratio scheme, a trend graph affecting the elastic modulus is drawn, and the primary and secondary order of the influence of various factors on the elastic modulus is analyzed;
[0095] S34. The longitudinal wave velocity test method is: use a pile foundation sonic tester to measure the sound wave propagation time of the sample, calculate the longitudinal wave velocity according to the sample height, take the average value of multiple samples in each mix ratio scheme as the longitudinal wave velocity test result of the mix ratio scheme, draw a trend chart of the factors affecting the longitudinal wave velocity, and analyze the order of priority of the factors affecting the longitudinal wave velocity.
[0096] In the specific example, the mass of the shock-absorbing grouting curtain material per unit volume is called the density of the shock-absorbing grouting curtain material. The calculation formula of the volume density method used in this test is shown in formula (2).
[0097]
[0098] Where: ρ is the sample density, g / cm 3 ; M is the sample mass, g; V is the sample volume, cm 3 .
[0099] According to the orthogonal test scheme in Table 2, three samples are prepared for each mix ratio scheme. The mass and size of the samples are measured by electronic scale and vernier caliper respectively. Then, the density of each sample is calculated according to formula (2). The average density of the three samples cast for each mix ratio scheme is taken as the density of the mix ratio scheme. According to the orthogonal test design in Tables 1 and 2, the average values of the three levels under the same factor are calculated. The trend diagram of the influence of each factor on the density is drawn according to the average values of the three levels under the same factor, as shown in Figure 2. Figure 4As shown in (a) in the figure. Through analysis, it can be seen that the order of influence of each factor on density is A>E>D>C>B. The density test results of this embodiment are shown in Table 5.
[0100] Table 5 Density orthogonal test results
[0101]
[0102] The uniaxial compressive strength of the shock-absorbing grouting curtain material is its main ability to resist external loads. The calculation formulas of various physical quantities in the test are as follows:
[0103]
[0104] Where: c is the uniaxial compressive strength, MPa; P max is the maximum breaking load of the specimen, N; A is the compressive area of the specimen, mm 2 ; E is the elastic modulus of the sample, MPa; σ c(50) 50% of the uniaxial compressive strength of the sample, MPa; ε h(50) Represents the axial strain corresponding to 50% of the uniaxial compressive strength.
[0105] According to the stress values of three specimens of each mix ratio at the time of failure recorded in the uniaxial compressive test and formula (3), the average uniaxial compressive strength of three specimens of each mix ratio is obtained as the uniaxial compressive strength of the mix ratio. According to the orthogonal test design in Tables 1 and 2, the average values of the three levels under the same factor are calculated, and the trend diagram of the influence of each factor on the uniaxial compressive strength is drawn according to the average values of the three levels under the same factor, as shown in the figure. Figure 4 As shown in (b). Through analysis, it can be seen that the order of influence of various factors on the uniaxial compressive strength of the shock-absorbing grouting curtain material is C>E>B>D>A. The uniaxial compressive strength test results of this embodiment are shown in Table 6.
[0106] Table 6 Results of orthogonal test on uniaxial compressive strength
[0107]
[0108] According to the axial stress and axial strain values of the three specimens of each mix ratio recorded in the uniaxial compression test and formula (4), the elastic modulus of each specimen can be calculated, and then the average elastic modulus of the three specimens of each mix ratio can be calculated as the elastic modulus of the mix ratio. According to the orthogonal experimental design in Tables 1 and 2, the average values of the three levels under the same factor are calculated, and the trend diagram of the influence of each factor on the elastic modulus is drawn according to the average values of the three levels under the same factor, as shown in the figure. Figure 4As shown in (c). Through analysis, it can be seen that the order of influence of various factors on the elastic modulus of the shock-absorbing grouting curtain material is E>C>B>D>A. The elastic modulus test results of this embodiment are shown in Table 7.
[0109] Table 7 Elastic modulus orthogonal test results
[0110]
[0111] During the acoustic wave test, a transmitting source emits a high-frequency pulse wave into the medium, and a receiving system records the propagation characteristics of the wave.
[0112]
[0113] Where: u, v, w represent the displacement in the x, y, z directions of the coordinate axis respectively; is the Laplace operator; G is the shear modulus; λ is the Lame coefficient; e is the volume strain symbol of the unit cell, e = ε x +ε y +ε z .
[0114] The equation for the longitudinal (P) wave velocity is:
[0115]
[0116] The RSM-SY6 pile acoustic wave tester is used to measure the longitudinal wave velocity of each sample. Then, the average longitudinal wave velocity of the three samples of each mix ratio is obtained as the longitudinal wave velocity of the mix ratio. According to the orthogonal experimental design in Tables 1 and 2, the average values of the three levels under the same factor are calculated. The trend diagram of the influence of each factor on the longitudinal wave velocity is drawn based on the average values of the three levels under the same factor, as shown in the figure. Figure 4 As shown in (d). Through analysis, it can be seen that the order of influence of various factors on the longitudinal wave velocity of the shock-absorbing grouting curtain material is E>D>C>A>B. The longitudinal wave velocity test results of this embodiment are shown in Table 8.
[0117] Table 8 Orthogonal test results of longitudinal wave velocity
[0118]
[0119] Specifically, in one embodiment of the present invention, step S4 includes:
[0120] S41, impact loading is performed on each sample, and the strain values on the incident rod and the projection rod of the sample during the impact process are recorded;
[0121] S42, drawing an energy dissipation curve of the sample according to the recorded strain value;
[0122] S43, calculating the energy transmittance ratio of each sample, and taking the average value of multiple samples in each ratio scheme as the energy transmittance of the ratio scheme;
[0123] S44. Calculate the average value of the multi-level ratio schemes under the same factor, draw a trend chart of the influence of each factor on the energy transmittance, and analyze the order of importance of each factor's influence on the energy absorption performance.
[0124] In a specific example, a split Hopkinson pressure bar test is carried out, and the strain values of the incident bar and the projection bar of each sample during the impact process are recorded to obtain the sample energy dissipation curve. Then, the average transmission energy ratio of the three samples of each ratio scheme is obtained as the transmission energy ratio of the ratio scheme. According to the orthogonal experimental design of Tables 1 and 2, the average values of the three levels under the same factor are calculated, and the following is obtained: Figure 5 The trend graph of the energy transmittance of the sample is shown. Through analysis, it can be seen that the order of influence of each factor on the energy absorption performance of the shock-absorbing grouting curtain material is E>C>D>B>A. The energy transmittance test results of this embodiment are shown in Table 9. The energy consumption of the sample is directly proportional to the shock-absorbing performance of the sample. The greater the energy consumption, the better the shock-absorbing performance of the material. All five factors have the performance of increasing the consumption of seismic wave energy, and the water-cement ratio has the least effect on them.
[0125] Table 9 Energy transmittance orthogonal test results
[0126]
[0127] Specifically, in one embodiment of the present invention, in step S5, the process of determining the optimal ratio of the grouting material includes:
[0128] According to the requirements of the proportion of curtain grouting materials, set the energy absorption performance, density and longitudinal wave velocity as high priority;
[0129] According to the priority order of each factor's influence on water separation rate, the priority order of each factor's influence on viscosity, the priority order of each factor's influence on density, the priority order of each factor's influence on uniaxial compressive strength, the priority order of each factor's influence on elastic modulus, the priority order of each factor's influence on longitudinal wave velocity, the priority order of each factor's influence on energy absorption performance and priority setting, the optimal level of each factor is selected, the specific value of each factor is determined, and the best ratio scheme is formed.
[0130] In step S5, the rationality of the optimal ratio scheme is verified by combining the theoretical analysis of the transflective performance of the grouting material, including:
[0131] Establish a transflection calculation model for grouting materials;
[0132] Based on the transflection calculation model, the P-wave and S-wave transmission coefficients of the best matching scheme under different incident angles are calculated;
[0133] Select the target incident angle and compare and analyze the transmission coefficients of the optimal ratio scheme and other ratio schemes;
[0134] Verify the rationality of the optimal ratio scheme through the comparison results of the transmission coefficients.
[0135] In a specific example, the specific process of step S5 is as follows:
[0136] The grouting curtain material should, on the basis of meeting the fluidity of the slurry, strive to minimize the impact of blasting seismic waves on buried pipelines. Therefore, it needs to have excellent energy dissipation performance and certain strength at the same time. Thus, the energy absorption performance, density, and acoustic wave velocity are given priority. Considering all these factors, the final selected optimal ratio is A2B3C3D3E2, that is, the water-cement ratio is 0.85, the mesh number of iron powder is 800 mesh, the iron powder content is 15%, the mesh number of rubber is 100 mesh, and the rubber content is 20%. At this time, the bleeding rate of the slurry is small, and the viscosity is maintained at about 22 s, and the grouting of the composite slurry will basically not cause blockage. The material ratio of this scheme is shown in Table 10.
[0137] Table 10 Optimal ratio scheme F-28
[0138]
[0139] For the theoretical analysis of the transmission and reflection performance of the grouting curtain material, the fill on both sides of the grouting curtain material is simplified to a viscoelastic medium, and at the same time, the grouting curtain material conforms to the deformation law of a viscoelastic body. Based on this, the theoretical model as shown in Figure 6 can be established.
[0140] Suppose a seismic source in the fill medium I excites a displacement amplitude of A ip1 , and its displacement function can be expressed by formula (9).
[0141]
[0142] Based on this function, the transmission and reflection of the stress wave are as follows: in the region where z < 0 (i.e., in medium I), a reflected P-wave with an amplitude of A rp1 and an SV-wave with an amplitude of B rs1 are generated. In the region where 0 < z < h, a P-wave with an amplitude of A tp2 and an SV-wave with an amplitude of B ts2 are generated, as well as a reflected P-wave with an amplitude of A rp2 and a reflected S-wave with an amplitude of B rs2 ; in the region where z > h, a transmitted P-wave with an amplitude of A tp3 and a transmitted SV-wave with an amplitude of B ts3 are generated.
[0143] In the viscoelastic medium, the position vector and propagation attenuation vector are introduced, and the position vector r = xi1 + yi2. The potential function in the medium can be expressed as equation (10). i1 and i2 are unit vectors in the x and y directions, respectively. p and A p They represent the propagation vector and attenuation vector of the longitudinal wave, respectively, P s and A s They represent the propagation vector and attenuation vector of the shear wave respectively.
[0144]
[0145]
[0146] In soil medium I, the total potential function is:
[0147]
[0148] In concrete medium II, the total potential function is:
[0149]
[0150] In soil medium III, the total potential function is:
[0151]
[0152] According to Snell's law, the wave numbers of all seismic waves in the z direction are equal, that is:
[0153]
[0154] The boundary conditions of this model can be regarded as the continuity of the tangential shear stress and tangential displacement at the two interfaces, and the continuity of the normal stress and normal displacement. The boundary conditions in this case are expressed as shown in equations (16) and (17):
[0155] 1. When z = 0
[0156]
[0157] 2. When z = h
[0158]
[0159] In the formula, u x represents the horizontal displacement, u z represents the vertical displacement, σ zz represents normal stress, τ zx Represents shear stress, where the units are selected using the International System of Units, the unit of displacement is m, and the unit of stress is Pa.
[0160] The stress-strain relationship is:
[0161]
[0162] Where θ = ε y +ε x is the relative volume change; γ is the shear strain.
[0163] By substituting the optimal ratio parameters selected in Table 10 into the simultaneous equations, the transmission and reflection coefficient of the P wave incident from the soil medium I and propagating through the concrete medium II and finally transmitting into the clay medium III can be obtained as the incident angle changes. It can be found that when the incident angle of the blasting seismic wave is greater than 40°, the transmission coefficient of the shock-absorbing grouting curtain material begins to decrease rapidly, and the transmission coefficient is 0 when the incident angle of the blasting seismic wave is 90°, and total reflection occurs when the incident angle of the blasting seismic wave is 90°. The transmission coefficient of the S wave generated by the incident P wave of the blasting seismic wave passing through the medium I and II and at the interface between the medium II and the medium III is the largest at 60°, which is 0.19, which is smaller than the transmission coefficient of the P wave.
[0164] Considering the actual situation of the project, the P-wave transmission coefficient at 20° is selected for comparison. Figure 7 As shown in the figure, through comparative analysis, it can be seen that the selected optimal ratio scheme (F-28) has a smaller transflection coefficient and better transflection ability, which also confirms that the selected ratio is more appropriate.
[0165] Specifically, in one embodiment of the present invention, step S6 includes:
[0166] S61. Arrange acceleration sensors and earth pressure sensors in the on-site blasting test;
[0167] S62, forming a grouting curtain according to the optimal ratio scheme;
[0168] S63, respectively recording the acceleration and soil pressure data in the soil before and after the grouting curtain is formed;
[0169] S64. Compare and analyze the vibration propagation law and the change of pipeline strain before and after grouting;
[0170] S65. Calculate the damping rate of the grouting curtain based on the vibration parameters before and after grouting.
[0171] In a specific example, in order to further study the shock-absorbing performance of the grouting curtain material on the blasting vibration of the buried pipeline, this embodiment carries out a blasting test. The blasting test design diagram is shown in FIG. Figure 8 The data of acceleration and earth pressure in the soil before and after the grouting curtain is formed are statistically sorted, and the statistical data results are shown in Table 11.
[0172] Table 11 Acceleration and soil pressure before and after grouting
[0173]
[0174] From the data results in Table 11, it can be seen that the acceleration and soil pressure increase with the decrease of the distance from the explosion center, which is in line with the attenuation law of the blasting vibration wave. Before and after grouting, the acceleration and soil pressure values of the J3, T3 and J4, T4 measuring points have large changes, which indicates that the grouting curtain absorbs and reflects the seismic waves generated by the blasting.
[0175] The strains of the measuring points of the protected objects (buried pipelines) before and after grouting were statistically sorted out, and the statistical data results are shown in Table 12 and Fig. 9 As shown in Table 12 and Fig. 9 From the data results, it can be seen that the strains before and after the pipeline have a large attenuation, which is consistent with the acceleration and soil pressure in the previous article, and the attenuation amplitude is about 40%. Therefore, the grouting curtain material helps to attenuate the impact of blasting on buried pipelines and is conducive to protecting the blasting safety of buried pipelines.
[0176] Table 12 Pipeline strain before and after grouting
[0177]
[0178] It can be seen that the shock-absorbing performance of the grouting curtain material is significant. The grouting curtain can attenuate about 40% of the pipeline strain and attenuate the seismic waves generated by the blasting to a large extent. It plays a certain protective role in protecting the safety of buried pipelines and has practical engineering significance.
[0179] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for designing the proportion of low-transmittance and energy-absorbing curtain grouting materials, characterized in that: include: S1. Select the basic proportion material of the grouting curtain, carry out multi-factor and multi-level orthogonal experimental design based on the basic proportion material, form n proportion schemes, pour the grouting material according to the n proportion schemes, obtain multiple samples for each proportion scheme, and number the samples according to the proportion scheme to which they belong; S2. Perform rheological property tests on the samples, analyze the test results, and determine the order of influence of various factors on the rheological properties; S3. Conduct indoor physical and mechanical property tests on the samples, analyze the test results, and determine the order of importance of various factors affecting the physical and mechanical properties; S4. Conduct a split Hopkinson pressure bar test on the sample to obtain the energy dissipation curve of the sample, and determine the order of influence of various factors on energy absorption performance according to the energy dissipation curve; S5. According to the results of steps S2-S4, determine the best ratio of the grouting material, and verify the rationality of the best ratio by combining the theoretical analysis of the transflective performance of the grouting material; S6. Verify the shock-absorbing effect of the optimal ratio scheme through on-site blasting tests and calculate its shock-absorbing rate.
2. The method for designing the proportion of low-transmittance-energy-absorbing curtain grouting materials according to claim 1, characterized in that: The multi-factor multi-level orthogonal experiment in step S1 is a five-factor three-level orthogonal experiment. 27 (3 5 ) Orthogonal test table design experiment is carried out 3 3 = 27 kinds of mixing ratios, that is, n = 27; the five factors are: Factor A: water-cement ratio; Factor B: iron powder mesh size; Factor C: iron powder content; Factor D: rubber mesh size; Factor E: rubber content.
3. The method for designing the proportion of low-transmittance-energy-absorbing curtain grouting materials according to claim 1, characterized in that: The rheological property test in step S2 includes a water separation rate test and a viscosity test, and the physical and mechanical property test in step S3 includes a density test, a uniaxial compressive strength test, an elastic modulus test and a longitudinal wave velocity test.
4. The method for designing the proportion of low-transmittance-energy-absorbing curtain grouting materials according to claim 3, characterized in that: Step S2 includes: S21. The test method for water separation rate is as follows: the water separation amount is measured by using a measuring cylinder, the average value of multiple samples in each mixing ratio is taken as the water separation amount of the mixing ratio, the average value of the mixing ratios at multiple levels under the same factor is calculated, and a trend chart of the influence of each factor on the water separation rate is drawn, and the primary and secondary order of the influence of each factor on the water separation rate is obtained by analysis; S22. The viscosity test method is: use a standard funnel viscometer to measure and correct the data, take the average value of multiple samples in each mix ratio as the viscosity of the mix ratio, calculate the average value of multiple levels of mix ratios under the same factor, and draw a trend chart of the influence of each factor on the viscosity, and analyze the order of priority of the influence of each factor on the viscosity.
5. The method for designing the proportion of low-transmittance-energy-absorbing curtain grouting materials according to claim 3, characterized in that: Step S3 includes: S31. Density test method: use electronic balance to measure sample mass, use vernier caliper to measure sample height and diameter, calculate sample density according to mass-volume ratio, take the average value of multiple samples in each mix ratio as the density test result of the mix ratio, draw trend chart of factors affecting density, and analyze the order of influence of various factors on density; S32. The uniaxial compressive strength test method is as follows: a uniaxial compressive test is performed using a pressure testing machine, the maximum axial force when the sample is damaged is recorded, the uniaxial compressive strength is calculated according to the cross-sectional area of the sample, the average value of multiple samples in each mix ratio scheme is taken as the uniaxial compressive strength test result of the mix ratio scheme, a trend chart of factors affecting the uniaxial compressive strength is drawn, and the order of importance of various factors affecting the uniaxial compressive strength is analyzed; S33. The elastic modulus test method is as follows: during the uniaxial compression test, the axial stress and axial strain values of the sample in the elastic deformation stage are recorded, the elastic modulus is calculated according to the slope of the stress-strain curve, the average value of multiple samples in each ratio scheme is taken as the elastic modulus test result of the ratio scheme, a trend graph affecting the elastic modulus is drawn, and the primary and secondary order of the influence of various factors on the elastic modulus is analyzed; S34. The longitudinal wave velocity test method is: use a pile foundation sonic tester to measure the sound wave propagation time of the sample, calculate the longitudinal wave velocity according to the sample height, take the average value of multiple samples in each mix ratio scheme as the longitudinal wave velocity test result of the mix ratio scheme, draw a trend chart of the factors affecting the longitudinal wave velocity, and analyze the order of priority of the factors affecting the longitudinal wave velocity.
6. The method for designing the proportion of low-transmittance-energy-absorbing curtain grouting materials according to claim 1, characterized in that: Step S4 includes: S41, impact loading is performed on each sample, and the strain values on the incident rod and the projection rod of the sample during the impact process are recorded; S42, drawing an energy dissipation curve of the sample according to the recorded strain value; S43, calculating the energy transmittance ratio of each sample, and taking the average value of multiple samples in each ratio scheme as the energy transmittance of the ratio scheme; S44. Calculate the average value of the multi-level ratio schemes under the same factor, draw a trend chart of the influence of each factor on the energy transmittance, and analyze the order of importance of each factor's influence on the energy absorption performance.
7. The method for designing the proportion of low-transmittance-energy-absorbing curtain grouting materials according to claim 3, characterized in that: In step S5, the process of determining the optimal ratio of the grouting material includes: According to the requirements of the proportion of curtain grouting materials, set the energy absorption performance, density and longitudinal wave velocity as high priority; According to the priority order of each factor's influence on water separation rate, the priority order of each factor's influence on viscosity, the priority order of each factor's influence on density, the priority order of each factor's influence on uniaxial compressive strength, the priority order of each factor's influence on elastic modulus, the priority order of each factor's influence on longitudinal wave velocity, the priority order of each factor's influence on energy absorption performance and priority setting, the optimal level of each factor is selected, the specific value of each factor is determined, and the best ratio scheme is formed.
8. The method for designing the proportion of low-transmittance-energy-absorbing curtain grouting materials according to claim 3, characterized in that: In step S5, the rationality of the optimal ratio scheme is verified by combining the theoretical analysis of the transflective performance of the grouting material, including: Establish a transflection calculation model for grouting materials; Based on the transflection calculation model, the P-wave and S-wave transmission coefficients of the best matching scheme under different incident angles are calculated; Select the target incident angle and compare the transmission coefficient of the best ratio scheme with other ratio schemes; The rationality of the optimal ratio scheme is verified by comparing the transmission coefficient results.
9. The method for designing the proportion of low-transmittance-energy-absorbing curtain grouting materials according to claim 1, characterized in that: Step S6 includes: S61. Arrange acceleration sensors and earth pressure sensors in the on-site blasting test; S62, forming a grouting curtain according to the optimal ratio scheme; S63, respectively recording the acceleration and soil pressure data in the soil before and after the grouting curtain is formed; S64. Compare and analyze the vibration propagation law and the change of pipeline strain before and after grouting; S65. Calculate the damping rate of the grouting curtain based on the vibration parameters before and after grouting.
10. The method for designing the proportion of low-transmittance-energy-absorbing curtain grouting materials according to claim 1, characterized in that: The basic mix materials of the grouting curtain are cement, rubber powder, iron powder and river sand.
Citation Information
Patent Citations
Quick-setting type adjustable gel grouting material and application thereof
CN109608144A
Design method for mixing proportion of high-performance shield tunnel synchronous grouting material
CN112943274A
Wall back grouting radiography slurry and ultrasonic positioning method for diffusion process of wall back grouting radiography slurry
CN114634342A
Method for selecting clay cement slurry ratio
CN117388473A
Method for determining optimal printing parameters of FDM type 3D printer
WO2023178876A1